Comparative Analysis between Corporate Sukuk and Bonds in Indonesia: Value at Risk Approach - Putra, Bintang Fajar Muskan; Sukmaningrum, Puji sucia Sucia; Rusgianto, Sulistya (The Indonesian Capital Market Review, 2023)
This research aims to analyze the differences in Risk (Value at Risk) and Return between sukuk and bonds. The research approach utilizes the T-test to examine this comparison. The data source is the closing prices of Sukuk and Bonds for 2018-2020. The research results indicate a significant difference between Sukuk and Bonds regarding returns. A vital difference also occurs in Sukuk and Bonds's Value at Risk (VaR). The results of this study prove that Sukuk has higher returns and lower VaR than Bonds. Sukuk can be a good instrument for portfolio diversification.